Frequency, intensity and duration of routine rehabilitation exercises practiced by patients with coronary artery disease - Dania Mubashar; Arooj Fatima (Journal of the Pakistan Medical Association, 2021)
This article is designed to determine frequency, intensity and duration of routine rehabilitation exercises practiced by patients with coronary artery disease (CAD). Living a sedentary lifestyle along with unhealthy diet can also contribute to this disease. Cardiac rehabilitation is considered to play key role to prevent from these circumstances. Objective: To determine frequency, intensity and duration of routine rehabilitation exercises practiced by patients with coronary artery disease. Methodology: Cross-sectional descriptive study was conducted in Hospitals of Lahore. The research was completed within 5 months after the approval of synopsis from February – June 2019. Patients having unstable angina, exertional angina, and multiple organ failure will be excluded. The data was collected from 186 participants (105 males and 81 females) by using interview based questionnaire. Descriptive statistics including percentages, mean and frequency distribution were calculated for each variable. Results: The study included 105 males (56.5%) and 81 females (43.5%) showing that most of subjects with age ranges 52-62 years (n = 72), standard deviation (SD = 56.34), were affected with cardiac incident. It was noted that 117 subjects (62.9%) practiced brisk walking as their routine rehabilitation exercise with frequency of 57 subjects performed 3 times per week and 117 subjects with duration of 10-20 minutes. Continuous...